“Ele anunciará justiça às nações”: uma análise pragmalingüística do uso de Is 42.1-4 em Mt 12.18-21 - Souza, Ricardo Santos (2023)
Justice is one of the divine attributes and, at the same time, an anthropological desire. By means of the Covenant, God communicates his justice to his people and, subsequently, to the nations. Deutero-Isaiah, especially the first “Song of the servant of the Lord” (42:1-9), emphasizes that God chose a human agent to announce his justice to the Judahite exiles in Babylon and the surrounding nations. The Gospel according to Matthew, in turn, quotes this Isaian poem in one of its narratives (12.18-21) and applies it to the person and mission of Jesus of Nazareth, identifying him as “the Servant of the Lord”; the one who fulfills, communicates and realizes justice in human history. The text studied makes it possible to perceive a relationship of continuity between Jesus' mission and the Hebrew Scriptures (OT) with regard to the demand for justice promoted and desired by God, thus becoming the basis for the development of this dissertation. By means of a pragmalinguistic approach, an attempt is made to focus on the communicative dynamics of the text, highlighting its pragmatic axes, with the aim of awakening the modern reader to recognize the Servant who announces justice and to follow him in his words and actions